1965
DOI: 10.5006/0010-9312-21.10.316
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidation off Iron, Nickel and Cobalt-Base Alloys Containing Aluminum

Abstract: By conducting continuous weight-gain measurements from 500 to 1300 C on a variety of Fe-Al, Fe-Cr-Al, Ni-Al and Co-Al alloys in oxygen at 100 torr and examining the reaction products which form, reasons for the enexpected ineffectiveness of preferential aluminum oxidation have been explored. With Fe-4.4 percent Al and Fe-12 percent Al, there are two different regions of parabolic growth- these are associated with the appearance of γ-A12O3 below 900 C and α-Al2O3 above. The latter is normally mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(36 citation statements)
references
References 0 publications
3
32
1
Order By: Relevance
“…11), where there is no Cr in the alloy. These results are in agreement with the earlier proposals [12,11] …”
Section: Discussionsupporting
confidence: 83%
“…11), where there is no Cr in the alloy. These results are in agreement with the earlier proposals [12,11] …”
Section: Discussionsupporting
confidence: 83%
“…The results obtained in this study were similar to those found in the literature~oggs; DeVan , 1993z 1993bHagel;Prescott 1992% 1992bSaegusa;Sakiyama;Smith 1987c;Tomaszewski 1978Tomaszewski , 1983Tortorelli , 1993Tortorelli , 1994a. In general, the relative amount of scale development was found to decrease with increasing aluminum content and temperature.…”
Section: Oxidation Behavior Of Fe-al Alloyssupporting
confidence: 81%
“…In terms of the iron oxide that was found to grow on the scale, whether in nodule or continuous scale form, the results are again similar to that observed in the literature~oggs; Hagel;Prescott 1992b;Saegusa;Sakiyama;Smith 1987c;Tomaszewski 1981Tomaszewski , 1983. Growth of the oxides was predominantly by the outward difhsion of Fe cations to form an external layer of F~03 and Fe301.…”
Section: Oxidation Behavior Of Fe-al Alloyssupporting
confidence: 78%
See 1 more Smart Citation
“…Hagel reported a-alumina formation below 1 173 K and a-alumina above 1 173 K for Fe-22at%Al alloy. 15) Tortorelli also assigned the oxide as a-alumina from the kinetics curve of mass gain. 3) Additional experiment like isothermal oxidation tests should be conducted to assign the oxide.…”
Section: Discussionmentioning
confidence: 99%